Arabic Vocabulary Learning through Podcast-Based Stimulation in Informal Pesantren Settings - Nurul Fauzah (Civiliza Publishing, Indonesia., 2025)
Arabic vocabulary mastery is a crucial foundation for language proficiency in Islamic educational contexts, particularly in pesantren where Arabic functions as both a subject of study and a medium of daily communication. However, vocabulary learning among non-native Arabic learners is often constrained by classroom-centered instruction and limited exposure in informal environments. This study aims to examine how podcast-based audio stimulation implemented in informal pesantren settings supports Arabic vocabulary learning and to explore learners’ affective and behavioral responses to such stimulation. Adopting a qualitative research design with a naturalistic inquiry orientation, the study was conducted over a 12-week period at Pondok Pesantren Darullughah Wadda’wah. Data were collected through non-participant observations, learner reflections, and semi-structured interviews, and were analyzed thematically. The findings indicate that sustained exposure to Arabic podcasts in dormitory environments facilitates vocabulary development through gradual lexical noticing, increased familiarity with recurring lexical items, and emerging incidental use in peer interaction. In addition, learners demonstrated positive affective responses, characterized by reduced anxiety, sustained engagement, and tolerance of partial understanding. The study concludes that podcast-based stimulation functions effectively as incidental auditory input that enriches learners’ lexical environment beyond formal instruction. By embedding Arabic exposure into daily routines, podcasts offer a complementary and low-pressure approach to vocabulary learning in pesantren contexts. The findings contribute to discussions on informal language learning and provide pedagogical insights for integrating digital audio media into Arabic language education without increasing instructional burden.